Biotechnological Interventions Augmenting Livestock Health and Production - Mukhopadhyay, Chandra Sekhar; Choudhary, Ratan Kumar; Panwar, Harsh; Malik, Yashpal Singh (Singapore : Springer Nature Singapore : Imprint: Springer, 2023)
This book comprehensively discusses the applications of molecular genetics, functional and structural genomics, and proteomics vis-a-vis bioinformatics, artificial intelligence, and robotics in livestock healthfulness and productivity. It reviews the biotechnological approaches in veterinary sciences for increasing productivity and resistance to disease. The book emphasizes the approaches based on artificial intelligence to analyze the data collected on animals, pathogens, and their environment. It underscores artificial intelligence applications in disease diagnosis, epidemiological studies, and detecting biological phenomena, including heat-detection, pregnancy, docility, and infections. Further, the book examines the genomics and proteomics approaches for understanding the gut microbiota and the role of pathogen-host interactions in animal health and disease. Lastly, it explores both pathogenic and non-pathogenic microbial transfer between humans, animals, and the environment across one health spectrum.
Module 1_Functional Genomics and Proteomics -- Module 2_Microbial Genomics and Novel Biotechnological approaches to enhance animal health -- Module 3_Bioinformatics, Big Data, and Integrated Omics.
Keywords: Veterinary medicine; Genetics; Biotechnology; Veterinary Science; Genetics and Genomics; Biotechnology